Program Linier Parametrik - Simatupang, Adolf T (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to discuss a linear program problem where its constants can change, If a constant for a linear program problem is changed, then we don't need to count from the beginning again. Next, we will examine the properties of the objective function as a result of changes in these constants. In this discussion determine the non-negative